As relações de poder em uma cidade em ruínas: o lugar dos excluídos no romance Vencidos e Degenerados - PEREIRA, Paloma Veras (2018)
The present study aims to analize the novel Vencidos e Degenerados (1915), from the brazillian journalist and writer José do Nascimento Moraes, from the daily life of the excluded ones in a São Luís permeated by the discourse of the social decay experienced in the end of the XIX century and beginning of the XX century. For that, we discuss about two analytical views: the abolition of the slavery of the black and mixed people and the following place and discusses about them, also the conflicts in relation to the development of the letters fomented by the small group – intellectuals who, because of the position that they occupied in the society and the lack of investments to stay in their motherland have seen themselves privated in relation to the profession of writing and spreading their ideas. Based in this point of view, we will use as a theoretical contribution the discussions on assumptions of the relationship between Literature and Society, based, mainly, in Candido (2006), Compagnon (2010) and Pesavento (2003; 2004); aspects of the History of the state of Maranhão – based in Meireles (1960), Lima (2006; 2008; 2010), Viveiros (1954), Almeida (1983), among others – with emphasis in the periods of the Golden Age, also of the discourse of decline and the slavery; the panorama of the maranhense literature, concerning the symbolic significance of the Atenas Brasileira title –according to Leão (2013), Borralho (2010; 2011), Corrêa (2001; 2017) – and the period of the intellectual revival conceived by the group of the Novos Atenienses – concerning Lobo (2008) and Martins (2016) –, also we will highlight the role of the writer Nascimento Moraes in this movement; therefore, to conclude, we will stress the power relations and the problematic hero point of view, according to, respectively, Bourdieu (1989, 2004) and Lukács (2009). Intertwining the theoretical discussions presented to the narrative bulge of the work, we will observe that to be excluded, in São Luís of Vencidos e Degenerados, is to be the part of a city in material and moral ruins, traces associated with a decadence and a stagnation that reach everybody, especially those who are historically underprivileged and unassisted.